Cytological and physiological tolerance of transgenic tobacco to Cd stress is enhanced by the ectopic expression of SmZIP8. (June 2022) - Zou, Jinhua; Han, Jiahui; Wang, Yuerui; Jiang, Yi; Han, Bowen; Wu, Kongfen; Wang, Binghan; Wu, Yuyang; Fan, Xiaotan
Abstract: Zrt and Irt-like proteins (ZIPs) are responsible for transporting various divalent metal cations. However, information about the characteristics of the cellular and physiological tolerance of plant ZIPs to Cd stress is still limited. The expression levels of SmZIP 8 in Salix matsudana Koidz were upregulated by Cd stress. The complete length of SmZIP 8 from S. matsudana was cloned, and transgenic tobacco was obtained by Agrobacterium -mediated transformation. Then, the tolerance to Cd stress of wild-type (WT) and transgenic tobacco seedlings was analyzed and compared by studying the cytotoxicity of the root tip cells, photosynthetic parameters, histochemical staining of O 2− and H2 O2, the activities of antioxidant enzymes, and malondialdehyde content under Cd stress. In comparison with WT tobacco, the ectopic expression of SmZIP 8 in tobacco promoted the cytological tolerance of the transgenic tobacco to Cd stress by reducing cell damage, raising the mitotic indexes, and reducing the rate of chromosome aberration of the root cells. Meanwhile, the results of increased photosynthetic capacity, decreased oxidative damage, and activated antioxidant enzymes showed that the physiological tolerance of transgenic tobacco to Cd was enhanced. The principal component analysis for the above physiological parameters explained 96.08% of the total variance (PC1, 77.77%; PC2, 18.31%), indicating a significant difference in Cd tolerance abilities between the tobacco expressing SmZIP 8 and WT tobacco. Therefore, SmZIP 8 may be considered as an important genetic resource for the phytoremediation of Cd or other heavy metal pollution via the use of transgenic plants obtained through genetic transformation. Graphical Abstract: ga1 Highlights: The expression level of SmZIP gene was closely related with Cd stress. SmZIP Overexpression reduced Cd-induced cytotoxicity in transgenic tobacco roots. The physiological tolerance to Cd exposure of transgenic tobacco was promoted by overexpression of SmZIP .